Challenging Situations in the Treatment of Cancer-Associated Thrombosis - Balaian, Ekaterina; Marten, Sandra; Beyer-Westendorf, Jan; Trautmann-Grill, Karolin (Hämostaseologie, 2024)
Cancer-associated thrombosis (CAT) is a common clinical problem in the treatment of cancer patients posing some unique challenges. These include the need to balance between the risk of recurrent thromboembolic events and bleeding complications in the individual cancer patient. A frequently encountered dilemma is the need for long-term anticoagulation in the setting of active malignancy. Until now, optimal duration, intensity, and type of anticoagulation in cancer patients remain an area of ongoing debate. In this case-based review, we present several challenging clinical scenarios and provide guidance on management. For optimal treatment results, CAT generally requires a multidisciplinary approach including specialists for thrombosis and hemostasis as well as hematology and oncology. Individual patient preferences should always be taken into account, especially in clinical situations with weak treatment evidence.
Keywords: cancer; thrombosis; anticoagulation